Penegakan Hukum Terhadap Penyalahgunaan Sosial Media dalam Membangun Opini Publik pada Pemilu 2024 - Fransiskus Nomor; Ida Bagus Anggapurana Pidada; Kadek Fredi Andrika Adnantara (Lembaga Pengembangan Kinerja Dosen, 2024)
Perpetrators and parties related to misuse of social media in general elections, such as spreading fake news or hoaxes and spreading hate speech, may be subject to criminal sanctions as stated in the provisions of the article of the law. The method used in preparing this research is normative juridical with a conceptual approach and a statutory approach, especially the ITE Law, the Criminal Code to further examine law enforcement regarding the misuse of social media in building public opinion in the 2024 General Election (Pemilu).In practice, Law concerning Information and Electronic Transactions itself is still not effective because it is seen as tending to limit freedom of expression and bias in its implementation. There are no standard standards for determining activities that can be considered misuse of social media. Law Number 7 of 2017 concerning General Elections does not regulate the anticipation of misuse of social media in general elections using a repressive approach or imposing criminal sanctions.